Characterization of intersymbol interference in concentration-encoded unicast molecular communication - Mahfuz, Mohammad Upal; Makrakis, Dimitrios; Mouftah, Hussein T. (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
This paper characterizes intersymbol interference (ISI) in a unicast molecular communication between a pair of nanomachines in a nanonetwork. Correspondingly, a transmission-controlled approach based on reduced pulse-width transmission has been proposed in order to mitigate ISI. Binary amplitude modulation has been assumed for the concentration-encoded signaling. Characteristics of interference signal strength (as a fraction of total available signal strength at the location of receiving nanomachine) have been explained in terms of communication range, pulse-width, and data rate of the system. Performance evaluation has been explained in the form of improvement by reducing interference with a reduced pulse-width approach. Results based on numerical analyses with three suitable propagation media (air, water, and human blood plasma) have been shown for the sake of potential applications in the field of nano-bio-communication and healthcare nanomedicine. Finally, it is concluded that ISI is a significant issue in molecular communication, and the proposed reduced pulse-width based approach saves signal energy and improves ISI performance in concentration-encoded molecular communication.